How to construct a verifiable multi‐secret sharing scheme based on graded encoding schemes. (1st July 2019) - Hadian Dehkordi, Massoud; Oraei, Hossein
Abstract : In a verifiable multi‐secret sharing scheme, a dealer distributes multiple secrets between a group of participants and also additional information is given that allows each participant to check whether his share is valid. In this study, the authors present a novel verifiable multi‐secret sharing (VMSS) scheme with general access structure using monotone span programs, which its security is based on graded encoding schemes. More precisely, they reduce the hardness of graded decision‐Diffie–Hellman problem to the computational security of the authors' scheme in the standard model. To the best of the authors' knowledge, this is the first study to present a VMSS scheme based on graded encoding schemes.